2012
DOI: 10.1093/icesjms/fss179
|View full text |Cite
|
Sign up to set email alerts
|

Changes in distribution of Greenland halibut in a varying environment

Abstract: Morgan, M. J., Garabana, D., Rideout, R. M., Román, E., Pérez-Rodriguez, A. and Saborido-Rey, F. 2013. Changes in distribution of Greenland halibut in a varying environment. – ICES Journal of Marine Science, 70: 352–361. Fish are expected to respond to changing oceanographic temperature by altering their distribution. Off the coast of Newfoundland, Canada, there have been major changes in oceanographic temperature over the last several decades, with both record cold and record warm years being observed. Greenl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Greenland halibut, especially the young stages, have been shown to change their distribution to maintain preferred thermal habitats, migrating deeper or shallower depending on temperature conditions (Morgan et al, 2013;Wheeland and Morgan, 2019). Such migration possibilities would be very limited in the EGSL due to the geography and bathymetry of this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greenland halibut, especially the young stages, have been shown to change their distribution to maintain preferred thermal habitats, migrating deeper or shallower depending on temperature conditions (Morgan et al, 2013;Wheeland and Morgan, 2019). Such migration possibilities would be very limited in the EGSL due to the geography and bathymetry of this region.…”
Section: Discussionmentioning
confidence: 99%
“…Fish are remarkably sensitive to temperature changes (Steffel et al, 1976;Claireaux et al, 1995), and Greenland halibut (Reinhardtius hippoglossoides) has shown shifts in its distribution that are associated with changes in bottom water temperatures (Morgan et al, 2013;Wheeland and Morgan, 2019). Over the last few decades, bottom water temperatures in the Estuary and Gulf of St. Lawrence (EGSL) have been rising due to increased warm water pulses entering through Cabot Strait (Galbraith et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We next assessed whether temperature had an impact on the circulating microbiome signatures. Given the limited temperature tolerance of Greenland halibut 47 , we divided the populations into two groups based on whether they were sampled at temperatures below or above 5°C. Our results showed signi cant temperature-related differences in Greenland halibut at both the phylum and genus levels (Fig.…”
Section: Correlations With Biotic and Abiotic Factorsmentioning
confidence: 99%
“…In 2014, community members for the first time successfully fished from a larger vessel (~12.2 m) during the open water summer period (P. Kilabuk, personal communication), noting most vessels operated in Canadian Arctic communities are ~5.5 m long and too small to fish deep-water longlines. This is based on the assumption, however, that the loss of ice will not impact the overall food-web structure to such an extent as to modify the occurrence and abundance of Greenland halibut in the Sound (Morgan et al 2013). If this were to occur, over time, the fishery would likely transition to an open-water fishery with a longer fishing season as ice extent continues to decline.…”
Section: The Role Of Telemetry Data In Arctic Fisheries Managementmentioning
confidence: 99%
“…When considering long-term fisheries planning, the movement of the CSMB to the entrance of the Sound allows the community fishery to exploit the TAC across both winter and summer fishing areas and addresses the long-term climate scenario. This is based on the assumption, however, that the loss of ice will not impact the overall food-web structure to such an extent as to modify the occurrence and abundance of Greenland halibut in the Sound (Morgan et al 2013). Research is required to better predict the impact of sea-ice loss on deep-water ecosystems, especially when considering commercially important species whose populations will likely be placed under increasing pressure as the Arctic region becomes more accessible to fisheries (Steiner et al 2015).…”
Section: The Role Of Telemetry Data In Arctic Fisheries Managementmentioning
confidence: 99%